2022
DOI: 10.1021/acs.energyfuels.2c01583
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Variation on Water Micro-occurrence in Low-Rank Coals by a Low-Field Nuclear Magnetic Resonance Experiment: A Case Study of the No. 7 Coal Seam in Kongzhuang Coal Mine

Abstract: Determining the dynamic variation in water microoccurrence in the pore−fracture system of low-rank coal at different water saturations (S w ) is of great significance to reveal the water migration law of coal reservoirs during pressurized water injection. In this study, 10 low-rank coal samples were collected from the no. 7 coal seam of the Kongzhuang mine, Jiangsu Province, China, and the simulation experiments of water intrusive were used to study water micro-occurrence and dynamic variation in the coal pore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The transverse relaxation time ( T 2 , ms) can be expressed as T 2 = r ρ 2 F S where ρ 2 is the surface relaxation rate (μm/ms), r the pore radius (μm), and F S the geometry factor. The relationship between T 2 and r is proportional, so the pore distribution can be characterized by T 2. .…”
Section: Samples and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The transverse relaxation time ( T 2 , ms) can be expressed as T 2 = r ρ 2 F S where ρ 2 is the surface relaxation rate (μm/ms), r the pore radius (μm), and F S the geometry factor. The relationship between T 2 and r is proportional, so the pore distribution can be characterized by T 2. .…”
Section: Samples and Methodsmentioning
confidence: 99%
“…A T 2 value of 2.5–100 ms represents the seepage pores, corresponding to a pore size of 100–10 000 nm. A T 2 value of >100 ms indicates fractures, corresponding to pore sizes that are >10 000 nm. ,, …”
Section: Samples and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…By combining SEM and AFM, Li et al [19] found significant differences in the mechanical properties between the coal matrix and minerals, as well as far greater than average adhesion in pores near minerals. Li et al [26] used LF-NMR technology to accurately characterize the pore-fracture system of coal seam, studied the migration and occurrence law of fluid in coal pores under different saturation pressures, established the relative water saturation model of coal pores, and found that the pore and fissure would be destroyed under high saturation pressure, resulting in the decrease in coal water saturation. Liu et al [22] used µ-CT imaging technology to establish the micro-three-dimensional pore network ball and stick model of two kinds of coal in Qinshui Basin, and visualized the gas flow in the threedimensional structure.…”
Section: Introductionmentioning
confidence: 99%